Development of Moringa Leave Extract Nanoemulsions: effect of ethanol concentration and sonication toward the stability - Harimurti, Sabtanti; Febriyani, Dwi; Sukamdi, Dyani Primasari; Widada, Hari; Amid, Azura (EDP Sciences, 2024)
Preparation of serum in the form of extract nanoemulsions allows effective delivery of active ingredients to the skin due to the more stable nanoemulsions, lower viscosity, transparent visual aspects, and high surface area caused by the small globule size. This study aims to obtain an optimal 96% ethanol concentration and sonication time in forming stable nanoemulsions at temperatures of 4° and 40°C with an active ingredient of moringa leaf extracts. The experiment was performed in four sets of 96% ethanol concentration (5%, 10%, 15%, and 20%) and three sonication periods (30, 60, and 90 minutes). The freeze-and-thaw method was utilized to evaluate the stability of the nanoemulsions. The analysis unveiled that a 96% ethanol concentration of 10% and a sonication time of 46 minutes was the most appropriate formula, generating a particle size of 30.49 nm with a volume of 73.35%. At the same time, the stability test of the preparation revealed that storage time significantly affected the pH response. However, it did not significantly affect the viscosity response.